Penerapan Metode Drill Untuk Meningkatkan Kemampuan Berpikir Kritis Siswa Kelas VIII Materi Peluang - Rumondang Bulan Harahap; Adek Nilasari Harahap; Haritsah Hammamah Harahap (Program Studi Matematika Universitas Graha Nusantara Padangsidimpuan, 2025)
This class action research aims to determine the effectiveness of the application of the drill method in improving the critical thinking skills of grade VIII students in learning mathematics of chance material. The results showed a significant increase in students' critical thinking skills after the systematic and gradual application of the drill method. The average pre-test score in Cycle I increased from 52.00 to 71.33 with an N-Gain of 0.40 (medium category), and in Cycle II it increased further to 84.67 with an N-Gain of 0.47 (medium category). In addition, the percentage of student learning completeness increased from 53.33% in Cycle I to 86.67% in Cycle II. This improvement was also supported by students' increased active participation, seen from their courage to answer questions, ask questions, and discuss in small groups. Direct feedback from the teacher after practicing the problems also played a role in improving students' thinking processes and supporting the development of metacognition. The drill method proved effective in overcoming students' difficulties in summarizing opportunities, comparing probabilities, and constructing logical arguments based on mathematical data. Although the improvement in critical thinking skills is still moderate, this study shows that the drill method has great potential to be developed in learning mathematics, especially materials that require analysis and reasoning.